Diatom-based age pointers for sediment core PS58/266-3 - Torben Struve; Frank Lamy; Frederik Gäng; Johann Philipp Klages; Gerhard Kuhn; Oliver Esper; Lester Lembke-Jene; Gisela Winckler (PANGAEA, 2025)
This dataset contains the age tie points for core PS58/266-3 derived from diatom-based stratigraphy.
In: Struve, T et al. (2025): Sediment composition and particle flux reconstructions for the Southeast Pacific Antarctic Zone [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982690